The IN VITRO STUDY OF APOPTOSIS INDUCTION BY L-ASPARAGINASE OF ASPERGILLUS FUMIGATUS (ASPF-6) ON HUMAN LEUKEMIA CELL LINES: On Human Leukemia cell lines,HL-60 - VIPINA R; VIJAYA CHITRA A (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: L-Asparaginase is a relatively widespread enzyme used in the lymphoblastic leukemia chemotherapy. In the present investigation, we report new potential fungal L-asparaginase producer Aspergillus fumigatus from Kadalundi mangrove forest, Kerala. The aim of the present investigation was to evaluate the concentration-dependent cytotoxicity and apoptosis-inducing the effect of extracted enzyme and its ability to induce apoptosis against human leukemia cell lines-HL-60. Methods: The fungal strain was isolated by serial dilution method from rhizosphere soil of mangrove forest. The isolated enzyme purified by 80% ammonium sulfate precipitation, dialysis, and ion exchange chromatography. To determine cytotoxicity and level of apoptosis, three different tests were performed: (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide, JC-1 flow cytometry, and Annexin V/propidium iodide (PI) flow cytometric DNA fragmentation. The test compound efficiency compared with positive drug doxorubicin against HL-60 cell lines. Results: The test compound exhibited a concentration-dependent cytotoxic effect on proliferation of HL-60 cell lines (IC-50 12.39 U) with a different level of apoptosis induction (LR-11.3%). Conclusion: A. fumigatus derived L-asparaginase may be clinically useful and results in better utilization for limited fungal-derived drug resources and improve financial feasibility as a therapeutic option for human leukemia.